ENGLISH PRONUNCIATION LEARNING IN EFL CONTEXT: STUDENTS’ VOICE - neni winarti; monika monika; audi yundayani (Journal of English Language and Literature (JELL), 2019)
English pronunciation mastery is required by English as a foreign language (EFL) students. However, it seems difficult due to several reasons including the differences in producing the English letter comparing with the students’ native language. This study aims to identify the EFL students' voice in learning English pronunciation. A descriptive method was applied involving a group of 22 students from the English education program at STKIP Kusuma Negara, Jakarta, Indonesia as a subject of the research. The data of this study were obtained from an observation, a questionnaire, and a semi-structured interview. The results of this study indicate that all respondent realizes the importance of English pronunciation mastery. In addition, they found many challenges in pronunciation learning such as lack of English pronunciation ability, the influence of students’ mother tongue in producing the English words, uninterested pronunciation learning process, and low motivation in practicing to pronounce the English words. It is important for the English instructors to develop the strategy in delivering English pronunciation lessons based on students’ background including their characteristics as the EFL students.